FAKTOR – FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN INFORMASI CORPORATE SOCIAL RESPONSIBILITY (Studi kasus pada perusahaan LQ45 yang terdaftar di BEI tahun 2010 – 2011) (Students' Journal of Accounting and Banking, 2013)
The objective of this study is to examine the influence of firm size, profitability, size of the board of directors, company age, and institutional ownership to the corporate social responsibility disclosure in LQ45 companies that listed on the Indonesia Stock Exchange. The population are 90 LQ45 companies which listed on the Indonesia Stock Exchange at period 2010 to 2011. Sample was chosen by purposive sampling method amount 52 companies. Technique test of data is by using multiple linier regressions The result indicates that firm size, firm age and institutional ownership are significant positive influence on CSR disclosure. Profitability and size of the board of commissioners is not significant influence of CSR disclosure.Keywords: firm size, profitability, size oh the board directors, company age, and institutional ownership.